PENGEMBANGAN MODUL AJAR KEPOH (KOMIK EDUKASI PROFESOR HANA) MATERI PERUBAHAN WUJUD BENDA KELAS III SEKOLAH DASAR - Hafidzah Hafidzah; Nataria Wahyuning Subayani; Iqnatia Alfiansyah (JUSEDA, 2021)
Learning objectives can be realized optimally and cannot be separated from mutual support of compenents in learning both educators, students, and teaching material. Teaching materials in learning can be form of game media, visual media, audio-visual media, and media from of books. Teaching materials can help achieve the learning objectives. One alternative is to use modules from comic as teaching materials. This research aims to KEPOH (Komik Edukasi Profesor Hana) material changes in the form of objects in grade III elementary school worthy of use. The method used in this research is the ADDIE development model (Analysis, Design, Development and Implementation, Evaluation). In determining the feasibility of the module, validation is carried out on content aspects, presentation aspects, linguistic aspects, and graphic aspects in accordance with the eligibility criteria for textbooks according to BSNP (National education standards agency). Based on the resultsof data analysis that has been carried out regarding the development teaching module of the KEPOH (Komik Edukasi Profesor Hana) material change in the form of objects in grade III elementary school, got a final score of 3,96 in the very good category so that the teaching module of KEPOH (Komik Edukasi Profesor Hana) material change in the form of objects in grade III elementary school is feasible to use based on the book eligibility criteria according to the national education standards agency (BSNP).